Stand and Wait - Pasquale S. Toscano (Disability Studies Quarterly, 2019)
No abstract available.
Keywords: disability; ableism; medical model of disability; spinal-cord injury; diagnostic odyssey; rehabilitation; osteoporosis; paralysis